Study of some physical Changes Using Sheep Fat on Meat Broiler - Al-Ali, Ammar Hamoud Haji; Soliman, Ghiyath (Journal of agricultural, environmental and veterinary sciences, 2022)
This study was conducted to find out the effect of adding sheep fat to Broiler meat on physical changes and determine the better percentage of fat added to the Broiler meat.The experiment was conducted on five groups of broiler meat to which different percentages of sheep fat were added, according to the following:B broiler meat only (control) To which nothing was added, B1 (15% fat percentage+ broiler), B2 (20% fat percentage+ broiler), B3 (25% fat percentage+ broiler), B4 (30% fat percentage+ broiler).Physical changes (water carryability and cooking loss) and sensory changes (color, smell, softness, taste, general evaluation) were studied.The results showed that the addition of 15% fat was the best among the study groups where a higher degree of sensory evaluation was observed, where the general acceptance in relation to the sensory properties, which includes both softness, taste, color and smell as well the results showed that the higher the percentage of fat added, the more the value of the cooking loss in addition to the ability to save water as the increased portability of water leads to further improvement in the quality of meat. Through the statistical study, there were significant differences in probability value (P
Keywords: Sheep fat; broiler meat; water carryability; cooking loss; sensory changes